Foundations of chemistry an introductory course for science students - Cranwell, Philippa B. 1985; Page, Elizabeth (Lecturer in Chemistry Education)
"Chemistry is a subject that underpins many other disciplines. At the heart of chemistry is the study of the elements that make up the periodic table, the reactions they undergo and the new compounds that are formed. Water is a compound that we are all familiar with, and most people know the formula for water is H2O even if they know nothing else about chemistry. The formula of water tells us that it is a molecule made up of two atoms of the element hydrogen and one atom of the element oxygen. In your course you will learn that the elements in the periodic table are composed of atoms, and that atoms are made up from smaller particles called protons, neutrons and electrons. It is the specific combination of protons, neutrons and electrons that gives each element its particular properties"--